2019
DOI: 10.4314/jasem.v23i5.21
|View full text |Cite
|
Sign up to set email alerts
|

Impact of climate variability on cassava yield in the humid forest agro-ecological zone of Nigeria

Abstract: This study examined cassava yield response to variable climate in the humid forest agro-ecological zone of Nigeria. The data employed for this study was sourced from the archives of Nigeria Meteorological Agency, Lagos State and Ogun State Agricultural Development Program, Abeokuta. Bivariate correlation, multiple regression and Z-distribution were employed for data analysis. Results show that monthly, seasonal and annual rainfall did not affect the yield of cassava but monthly, seasonal and annual minimum and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 6 publications
0
17
0
Order By: Relevance
“…Based on the deduction that rainfall, temperature and relative humidity do not significantly influence yam yield in Ikom LGA from 1990 to 2016, Adejuwon and Ogundiminegha (2019) were of the position that non-climatic factors have a greater influence on crop yield than climatic factors in the Humid Forest Agro-Ecological Zone of Nigeria. This is supported by a similar study/ ecological zone where Magna et al (2018) found out that climatic variables (i.e.…”
Section: Climate Variability and Yam Production In Ikommentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the deduction that rainfall, temperature and relative humidity do not significantly influence yam yield in Ikom LGA from 1990 to 2016, Adejuwon and Ogundiminegha (2019) were of the position that non-climatic factors have a greater influence on crop yield than climatic factors in the Humid Forest Agro-Ecological Zone of Nigeria. This is supported by a similar study/ ecological zone where Magna et al (2018) found out that climatic variables (i.e.…”
Section: Climate Variability and Yam Production In Ikommentioning
confidence: 99%
“…Climate variability plays a significant role in the performance of agricultural production (Adejuwon and Ogundiminegha, 2019). Important climatic elements for crop growth and yield include solar radiation, temperature and water or rainfall (Elijah et al, 2018).…”
Section: Research Articlementioning
confidence: 99%
“…Air temperature, relative humidity, and barometric pressure are main physical parameters for assessing weather and climate, and have direct effects on human health, ecology and agriculture (Fagerlund et al, 2019;Villalobos et al, 2016;Yu et al, 2018;Adejuwon and Agundiminegha, 2019). Novel machine/deep learning algorithms for developing predictive weather and climate models rely on massive global datasets (Dueben and Bauer, 2018;Scher, 2018;Racah et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Ogun State is one of the agrarian belts in Nigeria that is especially known for poultry production. The state is also sensitive to climate variability, especially rainfall and temperature (Adejuwon and Ogundiminegha, 2019). Aiyelokun and Odekoya (2016) reported that these two climate elements have recorded significant increasing trend since the 1990s mostly due to greenhouse gasses.…”
Section: Introductionmentioning
confidence: 99%